The Relationship Between Leg Length And Stride Length In Students Of The Medical Faculty Of General Achmad Yani University - Hindun Saadah; Dewi Ratih Handayani; Dian Rosdiani Fajrin (Sean Institute, 2023)
The foot is one part of the body that functions in the locomotion process, one of which is walking. Walking is a form of movement in which the centre of gravity of the body moves alternately on the right and left sides of the foot when touching the floor. Walking can be influenced by anatomical and physiological factors. The process of walking can be observed so that it can assess abnormalities in walking in a person that can interfere with activities. This study aims to determine the relationship between foot length and stride length. This study used a cross-sectional design with 60 adult subjects. The parameters measured were leg length, which is the distance drawn from the calcanea tuberosity to the tip of the longest finger, and stride length, which is the distance between the foot that makes initial contact with the other foot during the walking process. The subjects were selected by consecutive sampling. The data were analysed with Pearson correlation. The measurement results of the mean foot length in this study were 26 cm, and the mean stride length was 79.02 cm. The results of this study showed a strong and significant correlation between foot length and stride length. These results indicate that the longer the foot, the more it will help propel the foot when toeing off, so that the stride is longer.